How many DNA analyses are performed on adult sexual assault victims in Milan (Italy): A ten-year review. Issue 1 (December 2019) - Piccinini, Andrea; Bailo, Paolo; Vignali, Giulia; Barbara, Giussy; Gennari, Giuseppe; Di Candia, Domenico; Albertini, Valentina; Kustermann, Alessandra
Abstract: The aim of this study is to evaluate the actual use of serological/DNA analyses in the investigations carried out on adult sexual violence victims in Italy during the years 2006–2015. The victims were assisted in the largest Italian rape center, in Milan (Soccorso Violenza Sessuale e Domestica – SVSeD - Service for Sexual and Domestic Violence). The total number of sexual violence victims examined during the years 2006–2015 (adults and minors) was 3521, in 1697 of cases, biological evidence had been collected, while the number of adult victims (>18 y.o.) examined was 2300, in 1211 of cases biological evidence had been collected. Biological evidence was collected from the victims' bodies using two swabs in five anogenital areas (labia maiora, labia minora, perineum, perianal and anal/rectum regions) and two swabs in all other skin areas suggested by the victims as areas of possible contact (double swab technique). Clothes were also collected on a case by case basis for the search of biological stains. Despite the proper collection, handling and chain of custody for all the swabs/items collected, serological/DNA analyses were requested in 86 cases out of 1211 only (710%). This percentage dropped to 190% when considering adolescent victims (13–19 y.o.). The reason why Italian Magistrates make little use of the powerful tool of DNA analyses in sexual assault cases, still remains unclear. Legal and procedural aspects are therefore also discussed.